Upaya Pengendalian Diri Melalui Layanan Bimbingan Kelompok - Petrisia Anas Waluwandja; Zummy Anselmus Dami (Universitas Persatuan Guru 1945 NTT, 2018)
The purpose of this research is to know the influence of information services the purpose of this research is to investigate and find out the effort self-control through the tutoring service group in SMP Negeri 1 Tasifeto Timur, especially review and knowing the efforts of self-control when suggested, the effort of restraint when responding to the opinion, the efforts of self control when receiving feedback, and the efforts of controlling themselves when being and behaving. This type of research is quantitative descriptive, with a population of 122 students and a sample of 55 students. Sampling technique used was accidental sampling. Results found: 1) group tutoring service is beneficial in the effort self-control when the suggested 2) group tutoring service is beneficial in the effort self-control when responding to the opinions, 3) tutoring service the group is beneficial in the effort self-control when receiving criticism, and 4). Group tutoring service is beneficial in the effort self-control when being and behaving.